Relation among zootechnical performance, biochemical indicators, water quality, and small invertebrates (zooplankton) abundance reared in biofloc-supplemented systems - Ahmed Said Al-Souti; Marwa M. Zaher; Amr M. Helal; Dina T. Meshhal; Mansour D. H.; Afify D. G. Al-Afify; Mohamed M. Rafaey; Abeer El-Saharty; Ehab El-Haroun; Marian G. Nassif; Abdallah Tageldein Mansour; Abdallah Tageldein Mansour; et al. (Frontiers in Marine Science)
The present study was conducted to investigate the interaction of biofloc water supplementations and potential zooplankton abundance and structure in Nile tilapia Oreochromis niloticus-rearing systems on zootechnical performance and biochemical indicators. Nile tilapia juveniles (13.30 g and 9.50 cm) were randomly distributed into 18 fiberglass tanks (500 L/tank with a stocking density of 40 fish/tank) to start the feeding experiment for 60 days. Fish weights were recorded weekly to adjust the feeding rate at 3% of their biomass using a commercial diet. Compared to the control group (T0, zero biofloc water supplementation), the influence of five biofloc supplementation levels was applied as follows: 14.2, 28.4, 42.6, 56.8, and 71 g L−1 (T1, T2, T3, T4, and T5, respectively). The biofloc was prepared in an external fermentor fiberglass tank (300 L) and added to the fish tanks to keep the biofloc levels constant during the experiment. After 30 and 60 days of the experiment, the number of zooplankton was 46,501 and 24,537 Ind. L−1, respectively, which included four families (Rotifera, Copepoda, Cladocera, and free-living nematodes) with the domination of family Rotifera at 81.65% and 93.89%, respectively. The water quality indicated was within the standard values recommended for fish culture. Compared to those of the control group, the values of growth performance, whole-body biochemical composition, and blood biochemical indicators were significantly higher in biofloc groups than in the control group. Group T3 achieved the highest significant growth performance values. In comparison with the control group, T3 achieved the lowest number of cultures and the abundance of small invertebrate prey after 60 days of culture. The fish reared in groups T0 and T1 showed the highest significant urea content and the highest concentrations of liver function enzyme activities. Interestingly, compared to all groups, T3 achieved the best feed conversion ratio (FCR) value (1.68). Principal component analysis (PCA) and Pearson’s correlation coefficient confidence (PCCC) clarified a close positive relationship between T0 and T3 with the total individual, Rotifera abundance, and FCR. The highest PCCC value with T0 was in group T3 (0.947). In conclusion, biofloc supplementation (42.6 g L−1) showed a sustainable clean aquadiet strategy and significantly improved Nile tilapia growth and FCR with regard to the culture of small prey invertebrates for 60 days.